Imagined Bodies: Reading Gossip as Fiction - Bush, Catherine (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2014)
It can be useful to return to some fundamentals when thinking about what gives gossip its power, whether words spoken aloud or words that spread and leave their indelible traces throughout the digital realm. As a novelist and storyteller, I’d like to employ some lines of thought about what we do when we read fiction in order to consider gossip as an act of creative reading. Gossip, like a gift, depends on being received by someone, is defined by the intention to be received. Current fMRI studies have shown the empathetic capacities generated in individuals after reading works of fiction. I want to consider what happens when we imagine something about someone else, and how the engaged creativity of the recipient is essential to the act of gossiping.